The Application of Cloud Computing Technology in Computer Data Processing - Ma, Ruhui (Journal of Theory and Practice of Engineering Science, 2024)
In recent years, with the rapid development and continuous progress of cloud computing technology in China, it has provided a good platform for computer data processing work, played a role in promoting the progress of computer technology, has a wide range of applications, and can enhance the data processing level of computers, which is of great significance. Based on this, this article studies and analyzes the application value of cloud computing technology in computer data processing, and proposes several application suggestions, aiming to provide assistance in enhancing data processing effectiveness.